2018
DOI: 10.1002/er.4074
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on two-phase flow in a unitized regenerative fuel cell during mode switching from water electrolyzer to fuel cell

Abstract: Summary Mode switching between fuel cell and water electrolyzer of a unitized regenerative fuel cell alters two‐phase flow dynamics in the channels. To fully understand the mode switching, the observation of two‐phase flow is necessary. In this work, experiments are conducted to investigate the two‐phase flow in the flow field of a unitized regenerative fuel cell during mode switching. A transparent window is assembled at the oxygen side to allow a direct view of the serpentine flow field. The two‐phase flow a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The advantages of a PEM electrolyzer are high purity hydrogen production, the ability to work in high‐pressure circumstances, and the ability to store hydrogen fuel rapidly. This electrolyzer has high proton conductivity and impermeability characteristics of hydrogen output compared to the alkaline electrolyzer 39,40 . The use of solid polymeric membrane has a high potential for reacting as an excellent redox reaction barrier and gas separator, allowing for a compact cell construction with a fragile distance between a pair of electrodes and a decrease in the number of moving parts, making the structure easier to maintain 21,41 .…”
Section: Introductionmentioning
confidence: 99%
“…The advantages of a PEM electrolyzer are high purity hydrogen production, the ability to work in high‐pressure circumstances, and the ability to store hydrogen fuel rapidly. This electrolyzer has high proton conductivity and impermeability characteristics of hydrogen output compared to the alkaline electrolyzer 39,40 . The use of solid polymeric membrane has a high potential for reacting as an excellent redox reaction barrier and gas separator, allowing for a compact cell construction with a fragile distance between a pair of electrodes and a decrease in the number of moving parts, making the structure easier to maintain 21,41 .…”
Section: Introductionmentioning
confidence: 99%
“…On the aspect of experimental research, optical visualization, X‐ray radiography, MRI (magnetic resonance imaging), and neutron imaging are widely used methods 9 . Guo et al 10 utilized optical visualization to investigate the two‐phase flow in a unitized regenerative fuel cell. Dunbar and Masel 11 measured the water distribution in the flow field using MRI and found that the flow pattern in the flow field seems to be wavy‐stratified flow.…”
Section: Introductionmentioning
confidence: 99%
“…The distribution of gas-liquid two-phase flow in URFC is important in cell performance. Excessive liquid water easily causes water flooding and seriously hinders the normal operation of URFC due to the existence of gas and liquid in the cell during the actual operation [18][19][20][21][22][23] . Therefore, studying two-phase flow in simulation and reducing flooding phenomenon is important.…”
Section: Introductionmentioning
confidence: 99%